The under-reporting of sexually transmitted diseases cases: the Rio de Janeiro state’s situation - Luz, Tatiana CB; Pedrosa, Michele L (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the Sexually Transmitted Diseases (STD) are a major public health problem not only because of the morbidity of acute illness but alsobecause they enhance the sexual transmission of HIV infection. To facilitate disease control efforts it is important to implement a consistent and sim-ple surveillance system. In Rio de Janeiro State this system requires health care providers to notify six diseases and STD syndromic cases to theInformation System for Notifiable Diseases (Sinan). Objective:describe and compare the proportion of notifications by regions and cities of the Riode Janeiro State, asses the quality of these notifications and evaluate the level of under-reporting of STD cases. Method: descriptive study on 78,870notifications of STD cases from SINAN database between 2001 and 2004. Results:regions responsible for greater percentages of notifications wereMetropolitana 1 (54,6%), Baixada Litorânea (9,3%) and Serrana (7,8%). Sex and Age fields were properly filled. On the other hand, Race andEducational level weren’t fully completed and often were reported as ignored, hindering the access to information. There is a significative under-reporting of STD cases in the State and, from the period in study, 2004 showed the greatest percentage of notifications toward the estimated totalnumber of cases (2,12%). Conclusion:in the Rio de Janeiro State the SDT’s epidemiological surveillance system can’t be considered effective yet,due to under-reporting and low quality of information received. It is important to estimulate notifications and improve the quality of reported data.Keywords:Sexually Transmitted Diseases, SINAN, epidemiological surveillance, notification.